Nutritional Efficiency Wages and Unemployment: Where's the Beef?. (2nd September 2014) - Powell, Benjamin; Murphy, Ryan
Abstract: We modify the standard nutritional efficiency wage model to allow for the fact that employers can directly provide calories to their workers rather than paying a higher wage to induce employees to spend more on their own caloric consumption. We derive the various theoretical outcomes that are possible depending on the assumptions about the transaction costs of directly providing calories. We argue that in most real‐world situations the ability of employers to directly provide calories undermines the traditional efficiency wage theory as a cause of equilibrium unemployment.